2012
DOI: 10.5665/sleep.2108
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity after Adenotonsillectomy in Children with Obstructive Sleep Apnea during Wakefulness and Sleep

Abstract: Treatment of obstructive sleep apnea in children by adenotonsillectomy is associated with gradual improvement in known risk factors for cardiovascular disease. Complete normalization of baroreceptor sensitivity was not achieved 6 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…Nevertheless, the baroreflex system sensitivity is blunted in children with OSAS, not controlling exaggerated blood pressure variability . When SDB resolves, baroreflex sensitivity improves and blood pressure variability decreases . In addition, upper airway obstruction is accompanied by exaggerated negative intrathoracic pressure swings, increased systemic venous return, and preload to the right ventricle and decreased ejection fraction .…”
Section: Morbidity From the Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the baroreflex system sensitivity is blunted in children with OSAS, not controlling exaggerated blood pressure variability . When SDB resolves, baroreflex sensitivity improves and blood pressure variability decreases . In addition, upper airway obstruction is accompanied by exaggerated negative intrathoracic pressure swings, increased systemic venous return, and preload to the right ventricle and decreased ejection fraction .…”
Section: Morbidity From the Cardiovascular Systemmentioning
confidence: 99%
“…Several case‐control or uncontrolled studies have demonstrated resolution of subtle pathophysiologic and subclinical abnormalities related to OSAS in children following treatment interventions to relieve upper airway obstruction (Table ) . In the CHAT study, for each 5‐unit improvement in AHI and 5‐mmHg decrease in peak end‐tidal CO 2 , heart rate reductions by 1 and 1.5 bpm were measured, respectively .…”
Section: Morbidity From the Cardiovascular Systemmentioning
confidence: 99%
“…The presence of this feature indicates greater subject responsiveness to blood pressure regulation. Rates of change close to zero may indicate poor blood pressure control (Amin et al, 2008; Crisalli et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments suggest that this dysfunction may persist after resolution of sleep apnea. Studies in children looking at changes 6 months after adenotonsillectomy indicate that autonomic dysfunction estimated by LF/HF ratio and BRS substantially improve, but not completely and some evidence of dysfunction persists despite treatment (Crisalli et al, 2012; Muzumdar et al, 2011). These persistent changes may be related to inadequate resolution of OSAS or duration of follow up but certainly merit concern regarding their potential to contribute to long term cardiovascular morbidity.…”
Section: Physiological Effects Of Osasmentioning
confidence: 99%